Asesoris Memperindah Tampilan Baju Bodo - Muhammad Ardi; Srikandi Srikandi; Syamsiarna Nappu (DEDIKASI, 2018)
The partner of this Community Partnership Program (PKM) was a Silk Family UKM. The problems were:(1) lack of knowledge about bodo clothes (baju bodo) accessories design that has a beautiful appearance, (2) lacksthe skills to make bodo clothes accessories designs that have a beautiful appearance, (3) the quantity of productionof bodo clothes that have beautiful-looking accessories is very limited, and (4) the quality of the production of bodoclothes that have beautiful-looking accessories is very limited. The external target was a bodo clothes that hasbeautiful-looking accessories and a variety of colors for adults, teenagers, and children. The methods used were:lectures, demonstrations, discussions, question and answer, and accompanying partners. The results achieved were(1) the partner have knowledge in designing the bodo clothes (baju bodo) accessories, (2) the partner have the skillsto design and sew the accessories, (3) partners have the ability to increase the production of bodo clothes that haveaccessories with a beautiful appearance, (4) partners have the ability to improve the quality of bodo clothes that haveaccessories with a beautiful appearance, and (5) produce bodo clothes that have accessories of various colors with abeautiful appearance.